Relationship between gestational age, birth weight and deciduous tooth eruption - Afrin Mohamed Khalifa; Reyad Atef El Gendy; Mohamed Mahmoud Abd El-Mohsen; Ahmad Alsayed Hammour; Rasha Sabry Abd El Lateef Aly (SpringerOpen, 2014)
Background: Teething is a normal part of child growth and development. Growth parameters and feeding pattern may be determinants of the timing of teeth eruption in healthy infant. Primary tooth eruption may be affected by gestational age, postnatal nutrition, degree of prematurity as well as severity of neonatal illness. Objectives: The aim of this study was to evaluate the relation between gestational age, weight and neonatal illness to the time of eruption of the first deciduous tooth. Materials and methods: This study was a follow up prospective study carried out at the Bab El Sharia University hospital from October 2010 to October 2012. The study included 250 newborn from the obstetric department, from the NICU and from the outpatient clinics at the hospital. The babies were stratified according to gestational age to preterm (<37 weeks): 72 cases and full term (>37 weeks): 178 cases. The babies were followed from birth till the eruption of the first deciduous tooth. Results: There was a negative linear correlation between the time of the first deciduous tooth eruption and birth weight. The eruption of the first deciduous tooth was delayed in babies admitted to NICU specially if there was major interference such as intubation, mechanical ventilation. Conclusion: Delayed tooth eruption was related to lower birth weight and prematurity. The delayed eruption in preterm babies may be related to premature birth and not to a delay in dental development.